Integrating traditional medicine with network pharmacology for Alzheimer's treatment - Sunil Kumar Kadiri; Prashant Tiwari (Health Sciences Review)
A progressive neurological disease with a high global prevalence, Alzheimer's disease (AD) is characterized by memory impairment. Due to their primary focus on either a single signaling route or a particular molecular target, current treatment methods have shown limited success. An overview of the area is given in this review, along with an examination of possible supplementary remedies provided by traditional medicine, which takes a holistic approach. We examine attempts to combine network pharmacology, a cutting-edge method that offers deeper understanding of intricate biological processes, with traditional medicine. Compound-target interactions are examined via network pharmacology, which emphasizes the complementary benefits of traditional Chinese herbal remedies. Addressing the various pathways linked to AD enables it to target a variety of mechanisms, such as tau phosphorylation, oxidative stress, amyloid-beta accumulation, and neuroinflammation. Furthermore, the available evidence encourages pharmaceutical industries to consider herbs such as Ginkgo biloba, Curcuma longa, and Panax ginseng for AD management. Network pharmacology offers a valuable tool to validate their efficacy by predicting the molecular targets of compounds associated with amyloid-beta toxicity, tau hyperphosphorylation, and oxidative stress modulation. However, significant challenges remain in combining network pharmacology with traditional medicine, such as the standardization of herbal extracts and clinical validation of their effects. Despite being in its early stages, this multifaceted approach holds great promise for the development of more effective therapeutics with tangible clinical benefits for AD.